1998
DOI: 10.1089/apc.1998.12.463
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Medication Compliance in Patients with AIDS

Abstract: The paradigm of AIDS patient care has evolved to that of a chronic disease that is manageable with combination antiretroviral therapy. Intermittent adherence to antiretroviral regimens, however, has been associated with the selection of HIV mutations, resulting in drug-resistant virus. Medication compliance has become a vital component in the care of HIV-infected patients. This study was designed to assess the degree of medication compliance with zidovudine (ZDV) over a 2-month period among a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
2
8
0
2
Order By: Relevance
“…AZT was the most commonly reported medication among participants. Although other antiretroviral medications were reported, as shown below, consistent with a ® nding reported by Jeffe et al 14 , AZT was the most commonly recognized and reported antiretroviral. Parametric (Pearson's r) and non-parametric (Spearman's rho) correlational analyses were used to assess bivariate associations between self-reported compliance with AZT dosing and sociodemographic, drug use, sexual behaviour, and health belief variables.…”
Section: Methodssupporting
confidence: 83%
“…AZT was the most commonly reported medication among participants. Although other antiretroviral medications were reported, as shown below, consistent with a ® nding reported by Jeffe et al 14 , AZT was the most commonly recognized and reported antiretroviral. Parametric (Pearson's r) and non-parametric (Spearman's rho) correlational analyses were used to assess bivariate associations between self-reported compliance with AZT dosing and sociodemographic, drug use, sexual behaviour, and health belief variables.…”
Section: Methodssupporting
confidence: 83%
“…Targeting interventions to patients likely to have lower adherence may be a more useful approach. Adherence self-report measurements may overestimate adherence to study regimens, compared with more objective measurements, such as pill counts or medication-event monitors [42][43][44]. However, there has been a high correlation between self-reported and objective adherence measurements, and lower adherence by self-report has been correlated with lower virologic responses [43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Self-report, pharmacy records, and pill counts tend to overestimate patient adherence by anywhere from 20 to 30% (Burney et al, 1996;Farmer, 1999;Frick et al, 1998;Liu et al, 2001;Schwed et al, 1999;Wagner and Rabkin, 2000). Clinicians also tend to overestimate medication adherence and inadequately detect poor adherence (Miller et al, 2002).…”
Section: Introductionmentioning
confidence: 99%